In vivo cytochrome P450 activity alterations in diabetic nonalcoholic steatohepatitis mice. Issue 2 (6th October 2016) - Li, Hui; Clarke, John D.; Dzierlenga, Anika L.; Bear, John; Goedken, Michael J.; Cherrington, Nathan J.
Abstract: Nonalcoholic steatohepatitis (NASH) has been identified as a source of significant interindividual variation in drug metabolism. A previous ex vivo study demonstrated significant changes in hepatic Cytochrome P450 (CYP) activity in human NASH. This study evaluated the in vivo activities of multiple CYP isoforms simultaneously in prominent diabetic NASH mouse models. The pharmacokinetics of CYP selective substrates: caffeine, losartan, and omeprazole changed significantly in a diabetic NASH mouse model, indicating attenuation of the activity of Cyp1a2 and Cyp2c29, respectively. Decreased mRNA expression of Cyp1a2 and Cyp2c29, as well as an overall decrease in CYP protein expression, was found in the diabetic NASH mice. Overall, these data suggest that the diabetic NASH model only partially recapitulates the human ex vivo CYP alteration pattern. Therefore, in vivo determination of the effects of NASH on CYP activity should be conducted in human, and more appropriate models are required for future drug metabolism studies in NASH.